The antiproliferative effect of Chloroform fraction of Eleutherine bulbosa (Mill.) Urb. on 2D- and 3D-human lung cancer cells (A549) model - Zakaria, Nur Hannan; Saad, Norazalina; Che Abdullah, Che Azurahanim; Mohd. Esa, Norhaizan (Multidisciplinary Digital Publishing Institute, 2023)
Since lung cancer is the leading cause of cancer-related death worldwide, research is being conducted to discover anticancer agents as its treatment. Eleutherine bulbosa, a Dayak folklore medicine, exhibited anticancer effects against several cancer cells; however, its anticancer potency against lung cancer cells has not been explored yet. This study aims to determine the anticancer potency of E. bulbosa bulbs against lung cancer cells (A549) using 2D and 3D culture models, as well as determine its active compounds using gas chromatography-mass spectrometry (GC-MS) analysis. Three fractions of E. bulbosa bulbs, namely chloroform, n-hexane, and ethyl acetate, were tested for cytotoxicity using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium-bromide (MTT) and CellTiter-Glo. The antiproliferative effects of the most cytotoxic fraction against the 2D culture model were determined by a clonogenic survival assay and propidium iodide/Hoechst 33342 double staining, whereas the effects against the 3D culture model were determined by microscopy, flow cytometry, and gene expression analysis. The chloroform fraction is the most cytotoxic against A549 cells than other fractions, and it inhibited colony formation and induced apoptosis of A549 cells. The chloroform fraction also inhibited the growth of the A549 spheroid by suppressing the spheroid size, inducing apoptosis, reducing the proportion of CD44 lung cancer stem cells, causing arrest at the S phase of the cell cycle, and suppressing the expression of the SOX2 and MYC genes. Furthermore, the GC-MS analysis detected 20 active compounds in the chloroform fraction, including the major compounds of eleutherine and isoeleutherine. In conclusion, the chloroform fraction of E. bulbosa bulbs exhibit its antiproliferative effect on 2D and 3D culture models of A549 cells, suggesting it could be a lung cancer chemopreventive agent.